Grammatical issues in the interpretation of the "statement of meanings" by Abdul Qadir Mulla Huwaish (Grammatical study) - Esraa Aziz Aliwi (International Journal Of Management And Economics Fundamental, 2025)
This research aims to present the grammatical aspect in the interpretation of Sheikh Abdul Qadir Mullah Hawish in his book "Bayan al-Ma'ani", due to the importance of this aspect in understanding the meanings of Quranic verses within their linguistic context, grasping their implications and connotations, and uncovering the reasons behind specific grammatical analyses. Although the Sheikh does not extensively or deeply address the existing disagreements among grammarians regarding grammatical issues—except where necessary—our choice of this topic stems from the fact that Sheikh Mullah Hawish's "Bayan al-Ma'ani" is considered a unique model among studies that have tackled the interpretation of the Holy Quran in the Islamic world, based on the chronological order of revelation rather than the traditional order of the Quranic text. In this study, we focus on the key grammatical aspects highlighted by the Sheikh, especially where there are disagreements or variations in grammatical interpretations, supported by specific examples. However, this does not imply overlooking the rhetorical and linguistic elements also addressed in his work. We have simply confined this study to the grammatical dimension in line with the research scope.